‘ELECTION’ A Bibliometric Review From 2018 - 2024 In South East Asia - Alamsyah, Anggriani (JPW (Jurnal Politik Walisongo), 2024)
Elections play a crucial role in democratic processes in Southeast Asia, serving as a platform for political participation and governance. Despite its significance, a comprehensive bibliometric analysis focusing on this region remains limited. This study conducts a bibliometric analysis of Scopus indexed publications on"elections" in Southeast Asia from 2018 to 2024. A total of 100 articles from 68 sources with contributions from  248 authors were analyzed using Vosviewer and RStudio to identify prominent themes, collaborative networks, and emerging research trends. Indonesia emerged as the leading contributor, accounting for 98 publications, 68 citations, and10 collaborative works, followed by Malaysia and Singapore. Key themes included political media, electoral institutions, election violations, artificial intelligence, and gender politics. Notable emerging topics were the impact of social media on voter behavior, youth engagement, and electoral governance. The findings indicate that while Indonesia dominates electoral research in Southeast Asia, further studies could explore electoral reforms, digital political campaigns, and voter education. These insights provide valuable implications for policymakers in improving electoral governance.This bibliometric review provides a comprehensive overview of electoral studies in Southeast Asia, highlighting key research trends and identifying future research directions to strengthen democratic governance in the region.